#### Answer

$-\frac{15}{238}$

#### Work Step by Step

We are given that $a=-3$, $b=64$, and $c=6$.
Therefore, $\frac{2c+a^{3}}{4b+6a}=\frac{2(6)+(-3)^{3}}{4(64)+6(-3)}=\frac{12+(-27)}{256+(-18)}=\frac{12-27}{256-18}=\frac{-15}{238}=-\frac{15}{238}$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$-\frac{15}{238}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.